DNase I sensitivity of integrated simian virus 40 DNA. - Blanck, G (1984)
We undertook an analysis of integrated simian virus 40 (SV40) DNA to learn whether the DNase I-sensitive region is retained in the integrated array of mouse transformants. Our results indicate that full-length integrated SV40 chromatin retains a DNase I-hypersensitive region at the same point as in nonintegrated SV40 chromatin. Thus, the lack of a DNase I-hypersensitive region is not likely to be the reason for nonpermissivity of SV40 in mouse cells. In addition, results reported here indicate that a deletion of about 200 base pairs of DNA in the region of the DNase I-hypersensitive site severely reduces the sensitivity of integrated SV40 chromatin. This result is similar to a previously reported result obtained with deletion mutants of SV40 analyzed in the lytic cycle. It is the first report of a DNA lesion affecting DNase I hypersensitivity of a mammalian chromosome.